2017
DOI: 10.3390/bioengineering4030071
|View full text |Cite
|
Sign up to set email alerts
|

3D Bioprinting and In Vitro Cardiovascular Tissue Modeling

Abstract: Numerous microfabrication approaches have been developed to recapitulate morphologically and functionally organized tissue microarchitectures in vitro; however, the technical and operational limitations remain to be overcome. 3D printing technology facilitates the building of a construct containing biomaterials and cells in desired organizations and shapes that have physiologically relevant geometry, complexity, and micro-environmental cues. The selection of biomaterials for 3D printing is considered one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 132 publications
(166 reference statements)
0
32
0
Order By: Relevance
“…Human induced pluripotent stem cells derived cardiomyocytes (hiPSC‐CMs) seeded on these vascularized bioprinted scaffolds resulted in creating a mature and spontaneously contracting (75–80 beats min −1 ) endothelialized myocardial tissue. Providing a local elastic modulus and integrin based binding motifs similar to the native ECM of cardiac tissue, these materials help the cardiomyocytes to attach and mature . The natural polymer based bioinks thus provide an ideal environment for the cardiomyocytes to be functionally active in an in vitro culture .…”
Section: Introductionmentioning
confidence: 99%
“…Human induced pluripotent stem cells derived cardiomyocytes (hiPSC‐CMs) seeded on these vascularized bioprinted scaffolds resulted in creating a mature and spontaneously contracting (75–80 beats min −1 ) endothelialized myocardial tissue. Providing a local elastic modulus and integrin based binding motifs similar to the native ECM of cardiac tissue, these materials help the cardiomyocytes to attach and mature . The natural polymer based bioinks thus provide an ideal environment for the cardiomyocytes to be functionally active in an in vitro culture .…”
Section: Introductionmentioning
confidence: 99%
“…As tissue engineering techniques and tissue models continue to advance 1 , 3 , 22 , 26 29 , it is critically important to develop effective methods for the long-term culture, condition, and observation of tissue engineered constructs 5 , 7 , 8 , 12 , 17 , 21 , 26 . Therefore, advanced bioreactors are needed to advance biofabrication, bioprinting, and tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is one of the major causes of death globally. According to World Health Organization (WHO), cardiovascular disease accounts for more than one third of the total deaths each year [50,51]. Depending on severity, treatment solutions may require replacement of damaged vital vasculature, or even heart transplantation.…”
Section: Cardiovascularmentioning
confidence: 99%
“…The generation and use of human pluripotent stem cell (iPSCs) is of growing interest for many applications as they can differentiate into multiple cell lineages [50]. Zhang et al demonstrated a bioprinting methodology to fabricate Bioprinting DOI: http://dx.doi.org/10.5772/intechopen.81135 endothelialized myocardium using iPSCs [57].…”
Section: Cardiovascularmentioning
confidence: 99%